Policy Entrepreneurs and the Origins of the Regulatory Welfare State: Child Labor Reform in Nineteenth-Century Europe. Issue 1 (February 2018) - Anderson, Elisabeth
Industrial child labor laws were the earliest manifestation of the modern regulatory welfare state. Why, despite the absence of political pressure from below, did some states (but not others) succeed in legislating working hours, minimum ages, and schooling requirements for working children in the first half of the nineteenth century? I use case studies of the politics behind the first child labor laws in Germany and France, alongside a case study of a failed child labor reform effort in Belgium, to answer this question. I show that existing structural, class-based, and institutional theories of the welfare state are insufficient to explain why child labor laws came about. Highlighting instead the previously neglected role of elite policy entrepreneurs, I argue that the success or failure of early nineteenth-century child labor laws depended on these actors' social skill, pragmatic creativity, and goal-directedness. At the same time, their actions and influence were conditioned by their field position and the architecture of the policy field. By specifying the qualities and conditions that enable policy entrepreneurs to build the alliances needed to effect policy change, this analysis lends precision to the general claim that their agency matters.